Hom-Yang-Baxter Equations and Frobenius Monoidal Hom-Algebras - Yuanyuan Chen; Liangyun Zhang (Advances in Mathematical Physics, 2018)
It is shown that quasi-Frobenius Hom-Lie algebras are connected with a class of solutions of the classical Hom-Yang-Baxter equations. Moreover, a similar relation is discussed on Frobenius (symmetric) monoidal Hom-algebras and solutions of quantum Hom-Yang-Baxter equations. Monoidal Hom-Hopf algebras with Frobenius structures are studied at last.